Comparison of two different techniques of cooperative learning approach: Undergraduates' conceptual understanding in the context of hormone biochemistry. Issue 2 (7th December 2017) - Mutlu, Ayfer
Abstract: The purpose of the research was to compare the effects of two different techniques of the cooperative learning approach, namely Team‐Game Tournament and Jigsaw, on undergraduates' conceptual understanding in a Hormone Biochemistry course. Undergraduates were randomly assigned to Group 1 ( N = 23) and Group 2 ( N = 29). Instructions were accomplished using Team‐Game Tournament in Group 1 and Jigsaw in Group 2. Before the instructions, all groups were informed about cooperative learning and techniques, their responsibilities in the learning process and accessing of resources. Instructions were conducted under the guidance of the researcher for nine weeks and the Hormone Concept Test developed by the researcher was used before and after the instructions for data collection. According to the results, while both techniques improved students' understanding, Jigsaw was more effective than Team‐Game Tournament. © 2017 by The International Union of Biochemistry and Molecular Biology, 46(2):114–120, 2018.